Re-Membering the Body: Constructing the Self as Hero in In the Skin of a Lion - Overbye, Karen (Studies in Canadian Literature, 1992)
Michael Ondaatje’s In the Skin of a Lion is rife with living bodies which are more than machines used as a means of productions or shells of an essential self, bodies which experience physical sensations and are abused by hard labour and the deliberate infliction of pain. Heroism and story-telling inform the representation of bodies in the text; both Caravaggio and Temelcoff fulfill superior masculine stereotypes through their bodies. Patrick’s body reveals truths about himself and his situation; he eventually turns to female models of a relationship with one’s body (as patterned by Alice and Clara). When he chooses to tell Alice’s story to Harris, Patrick becomes the storyteller rather than the physically powerful hero, demonstrating that the body, though socially inscribed, can become a site of change.